A research protocol for a prospective, multicenter, cohort study on interferon therapy for chronic hepatitis B combined with metabolism-associated fatty liver disease to achieve clinical cure - Zhou, Daqiong; Zhang, Chao; Zhang, Lu; Jia, Jianru; Fu, Junliang; Cao, Zhenhuan (Frontiers in Public Health, 2025)
IntroductionThe incidence of chronic hepatitis B (CHB) combined with metabolism-associated fatty liver disease (MAFLD) is increasing annually, and the presence of MAFLD may influence the clinical assessment of viral activity and transaminase levels. However, it remains unclear whether MAFLD impacts the achievement of clinical cure in CHB patients treated with polyethylene glycol interferon (Peg-IFN).MethodsA prospective cohort study was conducted to enroll patients with dominant CHB (on NA treatment, HBsAg <1,500 IU/mL, HBeAg negative, HBV DNA <10 IU/mL) and patients with dominant CHB combined with MAFLD, all of whom were treated with Peg-IFN. The study aimed to assess the efficacy and safety of Peg-IFN treatment and to elucidate the effect of MAFLD on achieving HBsAg clearance in these patients. Additionally, the study explored the T-lymphocyte characteristics of patients with CHB combined with MAFLD, analyzed the role of T-lymphocytes expressing inhibitory receptors in HBsAg clearance, and investigated the immunological mechanisms of HBsAg clearance through single-cell transcriptome sequencing technology.Ethics and disseminationPatients will be recruited at four medical centers in Beijing and Hebei, and written informed consent will be obtained to inform participants of the purpose of the study, potential risks, and benefits. Ethical approval has been granted for the study, which will focus on 48-week HBsAg clearance, and a detailed follow-up and adverse event monitoring plan has been developed.Strengths and limitations of this studyStrengths are that this study fills the gap in treatment strategies for patients with CHB combined with MAFLD and provides important treatment guidance to clinicians; the multicenter design may increase the diversity of the sample size, reduce the bias of single-center studies, and improve the external validity of the results. Limitations are that interferon therapy is often associated with side effects, which may lead to lower patient adherence and affect long-term follow-up and outcome monitoring of the study; the heterogeneity of the MAFLD population may have different effects on the efficacy of interferon therapy.Clinical trial registrationhttp://www.chictr.org.cn/bin/project/edit?pid=231498, identifier ChiCTR2400084913.